PERANCANGAN APLIKASI PENJUALAN MOBIL BEKAS DI CV. SHANDY MOTOR BERBASIS WEB - Minarni, S.Si., M.T; Beri Antoni (ITP Press, 2013)
A very tight competition is currently trading world requires a good promotional strategy. Promotional strategies to attract and reach more consumers and also to meet the needs of consumers. CV. Shandy Motor is a car showroom that specializes in buying and selling used cars, promotions are still using paper facility, brochures, and other similar facilities. Barriers - the barriers that make it less effective promotional product. Therefore, the authors researched to design an